2005
DOI: 10.1093/jb/mvi124
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression of Human ST6GalNAc III: Restricted Tissue Distribution and Substrate Specificity

Abstract: We isolated human ST6GalNAc III cDNA clones. The typical cDNA clones predicted a type II membrane protein of 305 amino acids with a short cytoplasmic transmembrane domain of sixteen amino acids and a catalytic domain of 280 amino acids. A short form clone predicted a protein of 240 amino acids lacking 65 amino acids including the transmembrane portion. The alternative usage of the second exon seemed to generate these two transcripts. Both had two common regions found among sialyltransferases cloned so far, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Some of the data were essentially the same as reported in [21] and [23], but they were confirmed in this study using the identical conditions. Both enzymes showed activity toward fetuin, MSGG and sialyl Lc4 as well as GM1b.…”
Section: Hst6galnac III and Vi Synthesize Dsggsupporting
confidence: 86%
See 1 more Smart Citation
“…Some of the data were essentially the same as reported in [21] and [23], but they were confirmed in this study using the identical conditions. Both enzymes showed activity toward fetuin, MSGG and sialyl Lc4 as well as GM1b.…”
Section: Hst6galnac III and Vi Synthesize Dsggsupporting
confidence: 86%
“…Isolation of cDNA clones was performed as described previously [23]. Briefly, RT (reverse transcription)-PCR using a human brain cDNA library as template was performed with the sense primer 5 -GAATGTGGGCTGGAGAGGTC-3 and the antisense primer 5 -GCAGAGTCACCATCCACATC-3 using TITANIUM TM Taq DNA Polymerase (Clontech) as follows; 95…”
Section: Isolation Of Human St6galnac IIImentioning
confidence: 99%
“…The sialyltransferase encoded by ST6GALNAC3 is expressed in human spleen, kidney, lung, and brain and catalyzes the synthesis of branched-type disialyl structures by transfer of a sialic acid onto a GalNAc residue (35,36). Others have shown that GC isoforms differ with respect to the degree of glycosylation (4,37).…”
Section: Discussionmentioning
confidence: 99%
“…While ST6GalNAc1 prefers Tn antigen as an acceptor, ST6GalNAc2 favors T antigen and sialyl-T antigen (Table 1). ST6GalNAc3 and ST6GalNAc4 both synthesize disialyl-T antigen from sialyl-T antigen and disialyl-lactotetraosyl-ceramide - G D1α from sialyl-lactotetraosyl-ceramide - G M1b (Table 1) (35, 36). Both ST6GalNAc5 and ST6GalNAc6 show restricted specificity towards G M1b to synthesize G D1α (Table 1) (37, 38).…”
Section: B α26 Siaylation Of O-glycans and Its Impact On Cancer Promentioning
confidence: 99%